PERAN BAWASLU DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DALAM PENGAWASAN PEMILU DAN PILKADA 2024 DI KABUPATEN MANGGARAI BARAT - Veliktus Jebarus; Alfred Omri Ena Mau; Rouwland A.Benyamin; Dra Yaherlof Foeh (PT. Hasba Edukasi Mandiri, 2025)
Elections and regional elections are essential parts of Indonesia's democratic system that involve active public participation. The General Election Supervisory Agency (Bawaslu) plays a key role in enhancing public participation in election and regional election oversight. This study aims to analyze the role of Bawaslu in Manggarai Barat Regency in promoting public participation and identifying factors that hinder it in the 2024 General Election and Regional Election. Using a qualitative approach with a descriptive method, the research reveals that although there are programs designed to increase participatory oversight, there is a gap between planning and implementation on the ground. Factors such as limited access to information, low political awareness, and political culture influence are major barriers. Nevertheless, the increase in the number of public reports in the 2024 Regional Election indicates a rise in participation. The study provides recommendations to strengthen the capacity of supervisors and socialization strategies to achieve more effective and democratic oversight.